Community health initiatives improve diabetes and hypertension management in Wajir North Sub County - Hefow, Shamsa H.; Mapesa, Job; Juma, Rose (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetes and hypertension drive a heavy Non-Communicable Disease burden in Kenya’s arid and semi-arid lands. Community health initiatives, led by community health promoters, may close gaps in access, adherence, and self-management, yet their performance in pastoralist settings remains under-described. Methods: We conducted a cross-sectional survey of adults (n=378) living with both diabetes and hypertension in Wajir County, Kenya. Proportionate sampling covered seven wards. Structured questionnaires captured socio-demographics, Community Health Initiatives exposure, medication access and adherence, monitoring behaviors, and lifestyle practices, including diet, salt/sugar reduction, alcohol/tobacco, and physical activity. Analyses included descriptive statistics, χ² tests, and logistic regression for self-management outcomes. Results: Respondents were predominantly middle-aged, married, and low-schooled, with pastoralist and unemployed groups prominent, profiles that complicate clinic-based follow-up. Community Health Initiatives' reach and awareness were high, with common services including education, screening/referral, and medication navigation. Participation was associated with better-reported medicine access, more consistent blood pressure/glucose monitoring, and higher uptake of lifestyle changes. Persistent barriers included distance to facilities, medicine stock-outs, and out-of-pocket costs. Conclusion: In this underserved arid and semi-arid lands context, community health initiatives appear essential for translating knowledge into day-to-day diabetes and hypertension management. Strengthening low-literacy counseling, peer-supported activity, practical salt-reduction aids, alongside supply-chain reliability and mobile refills, could accelerate control. Findings support investment in integrated, culturally responsive community strategies to sustain primary health care for non-communicable diseases.